E-Mobility: Hindrances and motivators for policies implementation in India. (March 2023) - Arora, Sameer; Gargava, Prashant
Highlights: The transfer of technology from gasoline to electric vehicles is one of the most effective alternatives for reducing carbon emissions. Lack of infrastructure and high cost of electric vehicles is the prime hindrance in technology shifting. Environmental benefits are the primary motivator in selecting electric vehicles. Abstract: India is one of the world's growing economies and comes under the top five greenhouse gas (GHGs) emitters and working tirelessly to meet long-term objective of reducing GHGs emission by 33–35% from the 2005 level by 2030 by shifting to renewable energy and electric vehicles (EVs). Transfer of technology towards electric vehicles can significantly reduce emissions, as road transport causes tremendous annual emissions from fuel burning. Government of India (GoI) implementing several policies, schemes, and programs to influence the market and promote EVs over conventional passenger vehicles such as setting up of EVs manufacturing plants, in-house development of batteries, development of charging facilities at common public places, subsidy on purchase of EVs etc. This study was carried out to quantify India's present trend in adopting EVs over conventional vehicles, benefits of switching to EVs and modification in other transport polices for reducing GHG emissions and major challenges in implementation of EV policies on ground. The study found that E-mobility policies require coherence between the decision-makers, energy generators, manufacturers, and end consumers. The hindrances and motivators in the decision making and adoption of e-mobility are profusely discussed in this study. The lack of infrastructure is the major hindrance and government subsidiary on EVs is the primary motivator among various factors.